Strengthening Character Education in the Perspective of Local Wisdom in Aceh Province - Idris, M. Arif; Suroto, Suroto (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
The formulation of this research problem is strengthening character education from the perspective of local wisdom in Aceh Province. This study aims to determine the process of enhancing character education from the perspective of local wisdom in Aceh Province and its funding and inhibiting factors. This research uses qualitative methods—information obtained through interviews, observations, and documentation. Results of this study show that the process of strengthening character education in the perspective of local wisdom in Aceh Province through socialization with the community related to local wisdom, applying discipline, making good habits, providing encouragement and motivation to each principal, including local wisdom in the educational curriculum, making policies for implementing local wisdom, using regional languages, implementing malem sigampong, and providing a budget to support local wisdom. Furthermore, the supporting factors are the existence of TPQ, the presence of taklim assemblies, teachers, and instruments, the fact of regulations on the application of local wisdom, Islamic law, special autonomy, history, togetherness, harmonization, synchronization, and coordination as well as good relations between the relevant agencies and institutions. And the inhibiting factors are geographical location in the border area, various tribes, outside cultural influences, population mobility, family, environment, covid-19, and the absence of standard curriculum, references, modules, and documents on local wisdom.